Optimization of the Supply Chain in the Oil and Gas Sector in Türkiye - MNEIMNEH, BASSEL (İstanbul Kültür Üniversitesi, 2023)
With the increasing demand for energy, optimization of the supply chain become an important factor in field development strategies targeted to maximize efficiency of energy supply and long-term economic feasibility for the next upcoming years. Supply chain optimization is considered an efficient solution system to manage the desired production, reduced lead time, lower costs and satisfy customer needs by analyzing the resources and implementing of strategic decision into the competitive market. Effective delivery service through quality management, sustainability in the supply chain and innovative strategies applied in the industry are also main contributors in enhancing the supply chain in the oil & gas sector. In this study, the optimization model consists of various activities like measuring, analyzing, modelling, prioritizing, and implementing actions using the literature review and quantitative application studies including spatial simulation and survey questionannaire tackeling the market.
Türkiye Petrol ve Gaz Sektörü Tedarik Zincirinin Optimizasyonu
▪ Yüksek lisans tezi.
Keywords: Supply Chain Optimization; Strategic Decision; Effective Delivery; Quality Management; Sustainability; Innovative Strategies